Integrity of circulating cell-free DNA as a prognostic biomarker for vaccine therapy in patients with nonsmall cell lung cancer. (4th March 2021) - Waki, Kayoko; Yokomizo, Kanako; Yoshiyama, Koichi; Takamori, Shinzo; Komatsu, Nobukazu; Yamada, Akira
Abstract: Background: Many clinical trials of immune checkpoint blockade-based combination therapies are under way. Vaccine therapy is a promising partner of combination therapies. We have developed a personalized peptide vaccination and conducted clinical trials of it in patients with various cancers. At the present time, we have only a limited number of biomarkers related to the prognosis of vaccine-treated patients. Thus, new biomarkers are urgently needed. Methods: In this study, we investigated the plasma cell-free DNA (cfDNA) integrity—a ratio of the necrotic tumor cell-derived long cfDNA fragments to the total dead cell-derived short cfDNA fragments from genomic Alu elements—in patients with advanced nonsmall cell lung cancer during treatment with the personalized peptide vaccination. Results: We found that (1) the cfDNA integrity was decreased after the first cycle of vaccination, and (2) the patients with high prevaccination cfDNA integrity survived longer than those with low prevaccination integrity (median survival time (MST): 17.9 versus 9.0 months, respectively; hazard ratio (HR): 0.58, p = .0049). A similar tendency was observed in postvaccination cfDNA integrity (MST: 16.4 vs 9.4 months; HR: 0.65, p = .024). Conclusions: These results suggest that cfDNA integrity is a possible prognostic biomarker in patients treated with the personalized peptide vaccine.